Effects of SARS-CoV-2 Infection During Late Pregnancy on Early Childhood Development: A Prospective Cohort Study - Wu, Tianchen; Chen, Lian; Wang, Yuanyuan; Shi, Huifeng; Niu, Jieqiong; Yin, Xiaohan; Li, Mengshi; Tan, Chang; Jiang, Hai; Zheng, Danni; Wei, Yuan; Zhao, Yangyu; et al. (Frontiers in Pediatrics, 2021)
Background: There is little direct or indirect evidence of the effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy on early childhood development. Methods: We conducted a prospective, observational cohort study in China from May 1 to October 31, 2020, that enrolled 135 mother-infant dyads: 57 dyads in the infection cohort and 78 in the non-infection cohort. Among all infants, 14.0% were preterm birth in the infection cohort and 6.4% in the non-infection cohort. Participants were followed by telephone interviews to collect demographic characteristics, medical records of coronavirus disease 2019, breastfeeding data, and early childhood development was assessed by the Age and Stage Questionnaire (ASQ-3) and Age and Stage Questionnaire Social-Emotional (ASQ:SE-2) Chinese versions at 3 months after childbirth. We used multivariable Poisson regression models to estimate the relative risk (RR) of SARS-CoV-2 infection. Multivariable linear regression models and a mediation model were used to test the direct and indirect associations between SARS-CoV-2 infection and the ASQ-3 score. This study was approved by the Peking University Third Hospital Medical Science Research Ethics Committee (No. IRB00006761-M2020127). Results: In the infection cohort, 13.6% of the children showed social–emotional developmental delay, and 13.5% showed overall developmental delay. The corresponding rates in the non-infection cohort were 23.4 and 8.1%. Compared with the non-infection cohort, SARS-CoV-2 infection during pregnancy did not increase the risk of social-emotional (RR = 0.87, 95% CI: 0.51–1.49) or overall (RR = 1.02, 95% CI: 0.60–1.73) developmental delay. The mediation model showed that SARS-CoV-2 infection indirectly affected the ASQ-3 score by increasing the length of mother–infant separation. Conclusions: SARS-CoV-2 during late pregnancy did not increase the risk of developmental delay of the offspring 3 months after delivery. However, SARS-CoV-2 may have indirect effects on early childhood development by increasing mother-infant separation.